Gothic revival worldwide A.W.N. Pugin's global influence - Brittain-Catlin, Timothy 1961-; Maeyer, Jan de 1952-; Bressani, Martin 1957- (Leuven University Press, 2016)
The year 2012 marked the bicentenary of the gothic revival architect A.W.N. Pugin. His influence as a designer not only spread fast globally, but also played a leading part in the transformation of material culture from the mid-nineteenth century onwards. Pugin's work has been comprehensively reevaluated over the last decade. In this volume sixteen leading scholars from across the globe discuss Pugin?s direct influence on church architecture and furnishing. Beautifully illustrated with a large selection of new photography, "Gothic Revival Worldwide", the successor to the volume Gothic Revival published in 2000, reveals how Pugin's ideas played a profound role in the changing face of material reform in church architecture as an expression of the evolving identity of the churches across the world from North America to Mongolia and the South Pacific
Keywords: Pugin, Augustus Welby Northmore -- 1812-1852; Neugotik; Architektur; Aufsatzsammlung